Implementasi Nilai Nilai Pancasila Dalam Program CSR Perusahaan Untuk Keberlanjutan Lingkungan Pada PT Telkom Pekalongan - Dwirainaningsih, Yustiana; Mursidah; Andri Nur Cahyo (Diktum: Jurnal Ilmu Hukum, 2026)
This study aims to analyze the implementation of Pancasila values within the Corporate Social Responsibility (CSR) programs of PT Telkom Pekalongan, particularly those oriented toward environmental sustainability. The research is grounded in the urgency of integrating corporate social responsibility with the foundational philosophy of the state, which emphasizes a balanced interplay among social, economic, and environmental dimensions in sustainable development. Employing a qualitative method with a case study approach, the study seeks to obtain an in-depth and contextual understanding of the phenomenon. Data were collected through in-depth interviews, field observations, and documentation analysis of the company’s CSR initiatives. The findings demonstrate that the value of Divinity is reflected in the ethical commitment to environmental preservation, the value of Humanity is manifested in efforts to enhance public awareness of a healthy environment, the value of Unity is realized through multi-stakeholder collaboration, the value of Democracy is evidenced by community participation in planning and implementation processes, and the value of Social Justice is embodied in the equitable and sustainable distribution of program benefits. These findings affirm that the internalization of Pancasila values in CSR policies functions not merely as normative legitimacy but also as an effective institutional strategy for strengthening corporate sustainability governance and contributing substantively to sustainable development.